Bagaimana Mengelola Keuangan Sekolah yang Efektif dan Efisien? - Ananda, Helin Destria; Sopanah, Ana; Dewi, Indah (Magister Akuntansi Universitas Pancasila, 2023)
The BOS Fund is a government program that basically provides funding for non-personnel operating costs for basic education units as implementers of the compulsory education program. There is a new change, namely the Regulation of the Minister of Finance of the Republic of Indonesia number 119/PMK.07/2021 concerning the management of non-physical special allocation funds, where the distribution which was originally through RKUD is now directly to the school's account. The purpose of this study was to find out how effective and efficient the management of BOS funds was as well as the supporting and inhibiting factors and their efforts at UPT SDN Ngadri , Binangun District. The method used in this research is descriptive quantitative. The research data are primary and secondary data. The data collection techniques of this research are observation, interviews and documentation. The data analysis technique in this study used the Mardiasmo theory, namely the ratio of effectiveness and efficiency ratio to measure the effectiveness and efficiency of managing BOS funds. The results of this study indicate that the management of BOS funds has been effective and efficient based on predetermined value classifications.